2015
DOI: 10.1109/tdei.2014.004182
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multi-temperature calibration method for measuring dielectric properties of food

Abstract: In the most commonly used, open-ended coaxial probe method, dielectric properties of food products are measured after calibrating the instrument at 25 °C using air (open circuit), short (short circuit) and deionized water. Measurement accuracy may be compromised when dielectric properties are measured at temperatures other than 25 °C. The main objective of this study was to systematically perform calibration at multiple temperatures, quantify measurement errors and develop a method for multitemperature calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Dielectric properties were measured using the open‐ended coaxial probe method (E4991A, Agilent Technologies, Inc., Santa Clara, Calif., U.S.A.) coupled with a temperature controlled chamber (MCBH‐1.2‐.33‐.33‐H/AC, Cincinnati Sub‐Zero Products, Inc., Cincinnati, Ohio, U.S.A.). The instrument setup and calibration procedure was performed at 20 °C and is described in detail by Chen and others (). While the liquid yolk and white can be measured using the same test cell used by the aforementioned authors, the eggshells required a different test cell because it has been shown that the dielectric properties of powders are affected by density (Nelson ).…”
Section: Methodsmentioning
confidence: 99%
“…Dielectric properties were measured using the open‐ended coaxial probe method (E4991A, Agilent Technologies, Inc., Santa Clara, Calif., U.S.A.) coupled with a temperature controlled chamber (MCBH‐1.2‐.33‐.33‐H/AC, Cincinnati Sub‐Zero Products, Inc., Cincinnati, Ohio, U.S.A.). The instrument setup and calibration procedure was performed at 20 °C and is described in detail by Chen and others (). While the liquid yolk and white can be measured using the same test cell used by the aforementioned authors, the eggshells required a different test cell because it has been shown that the dielectric properties of powders are affected by density (Nelson ).…”
Section: Methodsmentioning
confidence: 99%
“…The dielectric properties of lasagna components were measured using a multipoint temperature calibration method (Chen and others ). The temperature‐dependent dielectric properties of lasagna components were shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, variants that may be equivalent to the isothermal condition are desirable from a practical point of view. In this work, heterothermal variant 1, 2 and 3 calibrations are investigated and compared with the isothermal case, since they are faster and require less complex apparatus or equipment, such as temperature controllers, samplers and microclimatic chambers [15]. The remaining heterothermal variants are not suitable from this point of view.…”
Section: Heterothermal Calibrationmentioning
confidence: 99%
“…Concerning the temperature of each standard, [9] reports that you can leave only the reference liquid at the temperature of measurement, with no evidence that it is effective. An assessment carried out by [15] demonstrates that the relative error of measurement increases with the thermal difference between the calibration temperature (T ) and the measurement temperature (T ), and that it is more significant for ′′ than for ′ . Obviously, the closer Tcal is to T , the less the error will be.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation